Active control of sound by means of digital equalizers - CIESIELKA, W.; GOŁAŚ, A. (Archives of Acoustics, 2006)
The article describes single-channel digital systems, enabling active sound control according to the set criterion. Theoretical fundamentals of these systems are based on digital filter theory, using which the digital graphic, phase, inverse and adaptive equalizers have been designed and programmed. The described systems have been implemented into two cards with signal processors TMS320C25 and TMS320C31 made by Texas Instruments. The article presents mathematical models of the above mentioned equalizers and results of the experimental tests, which verify their performance.